2012
DOI: 10.1375/twin.15.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Do Heritability Estimates of Political Phenotypes Suffer From an Equal Environment Assumption Violation? Evidence From an Empirical Study

Abstract: Using data from the Minnesota Twins Political Survey, this paper tests for the presence of unequal environments (EEA) by zygosity in political attitudes. Equal environment measures used include shared bedroom, friends, classes, and dressing alike. Results show an EEA violation at p < .05 in 5% of the models tested. The violations' impact on heritability estimates and their confidence levels appear random in magnitude and direction. No reasonable post hoc explanation emerged for understanding the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Distal influences are not unimportant; they increase the likelihood of related proximal influences, but rarely are they a specific and immediate impetus for behavior (McLeod and Kessler 1990). With regards to sources of individuals differences, there is limited evidence that distal factors such as region, marital status, or income, substantially moderate genetic or environmental variance components estimates of political attitudes (Hatemi, Funk, et al 2009; Hatemi et al 2012; Littvay 2012; Smith et al 2012). This may be in part because long-term contextual factors are captured within the larger trait, and distal traits are often confounded with potential self-selection or moderation effects.…”
Section: Rationale For the Study Of Gene-environment Interaction And mentioning
confidence: 99%
“…Distal influences are not unimportant; they increase the likelihood of related proximal influences, but rarely are they a specific and immediate impetus for behavior (McLeod and Kessler 1990). With regards to sources of individuals differences, there is limited evidence that distal factors such as region, marital status, or income, substantially moderate genetic or environmental variance components estimates of political attitudes (Hatemi, Funk, et al 2009; Hatemi et al 2012; Littvay 2012; Smith et al 2012). This may be in part because long-term contextual factors are captured within the larger trait, and distal traits are often confounded with potential self-selection or moderation effects.…”
Section: Rationale For the Study Of Gene-environment Interaction And mentioning
confidence: 99%
“…Nevertheless, a series of studies have empirically addressed this criticism regarding political orientations. Hatemi et al’s (2010) extended kinship analyses found no special twin environments existed for political attitudes; Littvay (2012) partitioned common variance into that which is shared and that specific to each twin, and found explicit differences in rearing had little influence on the heritability of attitudes or ideology; Smith et al (2012) relied on a gene-environment interaction design and found sharing a room, attending the same class and other similarity-in-rearing measures had almost no influence on the heritability of ideology. One of the most powerful tests for unequal environments on attitudes was conducted by Eaves et al (1997) and later by Hatemi, Funk, et al (2009), in which MZ and DZ twins were assessed for attitudes from ages 9-18 every 2 years.…”
mentioning
confidence: 99%
“…At the time, the vast majority of the discipline had little exposure to the natural sciences. But political scientists have been rapidly learning the new methods in genetics that have been developed in the past few years (Cranmer and Dawes 2012;Dawes and Fowler 2009;Hatemi, Funk, et al 2009;Littvay 2012;Loewen and Dawes 2012;McDermott and Hatemi 2011;Settle et al 2010;Settle, Dawes, and Fowler 2009;Stam, Von Hagen-Jamar, and Worthington 2012;Verhulst 2012;Weber, Johnson, and Arceneaux 2011), and we are now working directly with geneticists on a variety of political outcomes and behaviors (Arceneaux, Johnson, and Maes 2012;Benjamin et al 2012b;Eaves and Hatemi 2008;Fowler, Baker, and Dawes 2008;Hatemi et al 2007;Hatemi, Alford, et al 2009;Hatemi, Dawes, et al 2011;Hatemi, Gillepsie, et al 2011;Klemmensen et al 2011;McDermott et al 2009;Medland and Hatemi 2008;Verhulst and Estabrook 2012;Verhulst, Hatemi, Eaves 2012a;2012b;Verhulst, Hatemi, and Martin 2010). But political scientists have been rapidly learning the new methods in genetics that have been developed in the past few years (Cranmer and Dawes 2012;Dawes and Fowler 2009;Hatemi, Funk, et al 2009;Littvay 2012;Loewen and Dawes 2012;McDermott and Hatemi 2011;Settle et al 2010;Settle, Dawes, and Fowler 2009;…”
Section: Resultsmentioning
confidence: 99%